Preparation and Electrocatalytic Performance of Bi-Modified Quartz Column Particle Electrode for Phenol Degradation - Jiguo Huang; Haitao Chen; Shuo Pang; Gang Liu; Huanyu Cui; Lili Dong; Xingjuan Liu (Journal of Chemistry)
Bismuth oxide (Bi2O3) and its composites have good electrocatalytic performance. Quartz column is a good kind of catalyst carrier with the characteristics of high mechanical strength and good stability. A novel Bi-modified quartz column particle electrode (BQP) was prepared by the dipping-calcination method. The characterization results revealed that Bi2O3 was successfully loaded on quartz column. The optimum preparation condition was calcining at 550°C for 4 h. Electrocatalytic performance was evaluated by the degradation of phenol and the results indicated that the triclinic phase of Bi2O3 showed the best electrocatalytic property. Besides, when the dosage concentration of the particle electrode was 125 g/L and the electrolytic voltage was 12 V, the degradation rate of phenol (200 mg/L) reached the highest (94.25%), compared with 70.00% of that in two-dimensional (2D) system. In addition, the removal rate of chemical oxygen demand (COD) was 75.50%, compared with 53.30% of that in 2D system. The reusability and regeneration of BQP were investigated and the results were good. Mechanism of enhanced electrochemical oxidation by BQP was evaluated by the capture of hydroxyl radical.